Role of age in dynamics of autoantibodies in pediatric Celiac disease - Chiara Maria Trovato; Monica Montuori; Beatrice Leter; Ilaria Laudadio; Giusy Russo; Salvatore Oliva (BMC, 2023)
Abstract Background Celiac disease (CD) is characterized by elevated serum titers of autoantibodies IgA anti-tissue transglutaminase 2 (TGA-IgA) and IgA anti-endomysial (EMA), with small bowel mucosa atrophy. We evaluated age differences between CD children exhibiting variable antibody titers at diagnosis. Methods CD children diagnosed between January 2014 and June 2019, according to 2012 ESPGHAN guidelines were studied. All had EMA and TGA-IgA measurements, while a proportion of them underwent esophagogastroduodenoscopy (EGD). Patients were grouped based on serum TGA-IgA titers normalized to the upper limit of normal (ULN) and differences in median age (years) assessed by analysis of variance (ANOVA) and creation of orthogonal contrasts. Results CD was diagnosed in 295 subjects (median age: 4.4 [IQR: 2.60-8.52]) with a biopsy sparing protocol (high titer: ≥ 10xULN) and in 204 by EGD biopsy. Of the latter, 142 (median age: 8.5 [IQR: 5.81-11.06]) and 62 (median age: 9.5 [IQR: 6.26-12.76]) had a low (< 5xULN) and a moderate (≥ 5 < 10xULN) TGA-IgA titer, respectively. Potential CD was diagnosed in 20 patients (median age: 3.6 [IQR: 2.47-6.91]). The median age was significantly lower in the no-biopsy group (ANOVA: F(3, 516) = 25.98, p < .001) than in low- and moderate titer groups (p < 0.0001), while there was no statistical difference between biopsy-sparing and potential CD groups. Conclusion CD patients with greatly elevated antibody titers (≥ 10xULN) were diagnosed at an earlier age than those with lower titers. This may indicate that an increase in TGA-IgA is independent of age and suggests a polarization of autoimmunity in younger individuals with higher serum antibody levels.